منهجية القدامى في التصنيف لكتب الاختيارات الشعرية - كرباع, علي (University of Eloued جامعة الوادي, 2012)
المختارات الشعرية هي أحد الركائز لبناء النقد الأدبي غايتها تجسيد روح و ذوق العصر، و لذا كان اهتمام القدامى بها كبيرا و ذلك بالنظر في تلك الدواوين الشعرية و اختيار جيد النصوص فيها بحثا على القيمة الفنية و الجمالية و إبقائها حية مدى الأزمان و العصور، سعيا منهم في الحفاظ على تراثهم الأدبي متبعين طريقة التنقيب و التلقي و القراءة في اختياراتهم سواء كانت هذه المناهج قائمة على الذوق أو على الغرض الشعري. The poetic choices are one of the main factors for building literary criticism. Its purpose is to release time soul and time taste, there fore, the ancients were giving great deals of importance to that. In accordance to those poetic books and selections the best texts looking for the artistic value and beauty and keeping it alive along times and ages aiming to reserve there library traditions following the way of exploitation, reading and receiving in their choices. Either those methods were set for the taste or for the poetic purpose.
Keywords: المختارات الشعرية، النقد الأدبي، الشعر; Poetry anthology, literary criticism, poetry